Lean project management: application of lean principles to project management - Almeida, André Bernardo Lopes de (2017)
In today’s challenging business environments, competitive advantage is of utmost importance for organizations and there is a raising demand for profitable solutions that allow organizations to gain competitive advantage. Two of such profitable solutions are Project Management (PM) and Lean Thinking, recognized methodologies for management and production processes. This dissertation proposes a framework to accelerate the performance of projects through PM practices and lean principles. To develop the framework, Project Management Officers (PMOs) of renowned Portuguese companies are interviewed. In the first Stage, interviews are conducted aiming to identify key pain points in PM. Resulting from the first set of interviews, lean principles are applied to PM to remedy the identified pain points and develop a Lean Project Management Framework. The interviews identify the most critical knowledge areas in terms of pain points as Human Resources, Scope, and Procurement Management. In the second stage, experts’ feedback is used to validate the developed framework on four pillars: degree of understanding, alignment towards the major pain points, practical applicability, and orientation towards the final result. All the respondents conceded that the newly developed framework considered the major pain points and was oriented towards the final result, projects success. Nevertheless, some respondents considered that up-front lean knowledge is needed and suggested the development of a framework dictionary to improve understanding and practical applicability. The findings show that the use of traditional lean tools adapted to the PM context can aid in the continuous improvement of processes and practices by conferring role clarity, transparency, and reducing bottlenecks. The Lean Project Management Framework provides a viable approach to overcome the shortcomings of traditional PM practices.